Load Frequency Control in Multi-Source Power Generation Systems using Harris Hawks Optimization Algorithm - Karnavas, Yannis L.; Nivolianiti, Evaggelia (2022 International Conference on Communications, Information, Electronic and Energy Systems (CIEES), 2022)
One of the main problems of power generation systems (either isolated or interconnected) is related to the frequency regulation and the continuous effort to keep the frequency as stable as possible with respect to various load fluctuations. The subject of this paper is the optimization of load-frequency controllers of single-area multi-source power generating systems. Specifically, a specific model which emerge from the international literature is presented to be studied. The main goal is to tune the controller of each generating source i.e. find their optimal gains through bio-inspired optimization algorithms. The algorithms which were applied are the particle swarm optimization (PSO) algorithm-used as a benchmark- and the Harris Hawk Optimization (HHO) algorithm, as the proposed one. The integral-in-time absolute error (ITAE) performance index is the corresponding objective function. The systems are being studied in the environment of Matlab/ Simulink and the derivation of the (sub)-optimal gains of the controllers result from the proper use of a custom written Matlab script which implements the optimization procedure. The results obtained show that the HHO performs better than those obtained through PSO, particularly in the case where the nonlinearity of the system under consideration increases.